2011
DOI: 10.1002/bjs.7723
|View full text |Cite|
|
Sign up to set email alerts
|

Multicentre observational study of the natural history of left-sided acute diverticulitis

Abstract: Long-term risks of recurrent AD or emergency surgery were limited and colectomy did not fully protect against recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 53 publications
1
43
1
5
Order By: Relevance
“…The time interval claimed necessary to distinguish between the two episodes varies among authors, ranging between 1 [1], 2 [2,3] and 3 months [4]. …”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time interval claimed necessary to distinguish between the two episodes varies among authors, ranging between 1 [1], 2 [2,3] and 3 months [4]. …”
Section: Definitionmentioning
confidence: 99%
“…In order to gather information on the natural history of complicated colonic diverticular disease, a joint study group, the Italian Study Group on Complicated Diverticulosis (GISDIC) was formed in 1997 [3]. All consecutive patients with left-sided AD diagnosed clinically (abdominal pain, associated with leukocytosis (>11 × 10 9 ) and/or fever >38°C) and confirmed by imaging (CT scan, ultrasonography, water-soluble contrast enema) either alone or in combination and/or by operative findings, entered the study.…”
Section: Our Studymentioning
confidence: 99%
“…134 These data were confirmed in a large multi centre study, in which the recurrence rate for conser vatively treated patients was 17.2% versus 5.8% in surgi cally treated patients, with the need for emergency surgery in 6.9% versus 1.3%, respectively. 135 Recurrence rates per year in conservatively treated patients were, however, only 1.8% and 2.1% in two large studies. 135,136 Hence, patient age and comorbidities might strongly influence the decision for elective surgery.…”
Section: Interventional Therapy and Surgerymentioning
confidence: 95%
“…135 Recurrence rates per year in conservatively treated patients were, however, only 1.8% and 2.1% in two large studies. 135,136 Hence, patient age and comorbidities might strongly influence the decision for elective surgery.…”
Section: Interventional Therapy and Surgerymentioning
confidence: 95%
“…Several large, long-term studies involving patients initially admitted to hospital for acute diverticulitis have reported that the 5-year recurrence rate is up to 20%. [16][17][18] Several aspects of management after an acute episode (i.e., diet, antibiotic therapy and surgery) are discussed below.…”
Section: How Is Diverticulitis Currently Managed After An Acute Episode?mentioning
confidence: 99%